Fingerprinting characterization of sedimentary PAHs and black carbon in the East China Sea using carbon and hydrogen isotopes. (December 2020) - Wang, Yipeng; Li, Tiegang; Zhang, Rui; Russell, James; Xiao, Xin; Cheng, Yaxin; Zhang, Fan; Liu, Zhiyong; Guan, Minglei; Han, Qi
Abstract: In this study, we present the application of a dual-isotope approach for the source apportionment of polycyclic aromatic hydrocarbons (PAHs) and black carbon (BC) in the East China Sea (ECS). The δ 13 C and δ 2 H isotope signatures of the PAHs were determined from surface sediments collected from the ECS. A Bayesian Markov chain Monte Carlo (MCMC) model was used to the environmental source identifications with dual-isotope PAHs data. The results indicate that the coal combustion source is predominant (with average of 41%) in the ECS. Liquid fossil fuels combustion, biomass combustion, and petrogenic sources account for 23%, 20%, and 12% of the total PAH burden, respectively. Additionally, we also determine the stable and radio carbon isotopes (δ 13 C and Δ 14 C) of total BC in sediment samples of the ECS. The results demonstrate the quantitative source apportionments for different sources, reflecting the contributions of fossil fuels (coal combustion and petroleum-related emissions), biomass (C3 and C4 plants) combustion, and rock-weathering sources. The fossil combustion in BC accounts for 67%, with 23% for biomass sources, meanwhile the rock weathering source in BC is an average of 10%. These results show a remarkable similarity and extensive homologies at source apportionment of PAHs and BC in the ECS, even though some differences in source mechanisms and processes. These findings on the environmental source apportionment will provide a reference for improved emission inventories, and will help to provide guidance for the efforts to mitigate environmental pollution in the coastal areas and marginal sea. Graphical abstract: Image 1 Highlights: δ 13 C and δ 2 H isotope signatures of PAHs in ECS are detailed reported. Their isotopic compositions can allow source apportionment of PAHs. CSIA approach indicate coal combustion as primary source of PAHs in ECS. 14 C and 13 C of sedimentary BC were also studied. Fossil combustion was an important component of BC in ECS.